Desenvolvimento de "Tinta" com Pó de Cortiça com desempenho acústico optimizado - António P. O. Carvalho (2010)
This paper presents the analysis and development of a new product (paint), with the incorporation of powdered cork, to optimize its acoustic performance. Tests were performed in a reverberation room to analyze the variation on the sound absorption coefficient of an existing paint with the introduction of different amounts of powdered cork and also to compare these results with a titled "acoustic paint already available in the market. The tests were performed on two different base supports (wood and metal) and analyzed with different percentages of added powdered cork and with different thicknesses.